A study of profile of patients failing first line NACO recommended ART - Mittal, Mahim; Chand, Phool; Mall, Ashootosh Kumar (International Journal of Advances in Medicine, 2018)
Background: Failure of first line NACO recommended Therapy has been reported in 1-5% cases of HIV/AIDS. Various factors are associated with failure. This study describes the profile of patients failing first line ART (FLA) in a predominately lower socioeconomic population. The objective of the present study was to identify factors associated with failure of FLA. Methods: Retrospective data analysis of patients failing first line therapy. Epidemiological information, clinical parameters and laboratory reports were taken into consideration. Data was analysed as per standard statistical analysis. Results: Out of a total 3926 patients on first line ART for varying periods of time from our ART centre 54 patients were on second line ART. Males (2.20%) had a high failure rate than females (0.50%). The average time of failure was 64.11 months with a median of 56.50 months. 74.1% (40/54) of the patients had very low CD4 count at the time of initial diagnosis. Failure rate of FLA was higher in the patients having Stavudine based regimen (NRTI) (6.61%) and 3.64% in patients having Nevirapine based regimen (NNRTI). Conclusions: Second line therapy is required only in a small number of patients at present, but as it is related to the duration on first line ART and also with initial low CD4 count, more and more patients will require SLA in the near future.